Description of a new species of Miltochrista Hübner from Vietnam, with eight new combinations (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V. (Zootaxa, 2017)
Miltochrista Hübner, [1819] is a large genus of lichen-moths (family Erebidae, subfamily Arctiinae, tribe Lithosiini) including more than 160 valid species and widely distributed in Oriental and Palaearctic Regions. The genus for a long time was treated in a wide sense. Holloway (2001) treated as Miltochrista only a small group of species close to the type species of the genus Miltochrista miniata (Forster, 1771), resurrected genera Barsine Walker, 1854, and Lyclene Moore, [1860], and transferred the majority of former Miltochrista and Oriental Asura Walker, 1854 to these genera. Following Holloway’s concept, many species were described as Lyclene during last two decades (Černý & Pinratana 2009; Kirti & Gill 2009; Bucsek 2012; 2014; Dubatolov & Bucsek 2013; 2014; Wu et al. 2013; Černý 2016). Kirti & Singh (2016) synonymized Lyclene with Miltochrista, but, nevertheless, the status of Lyclene is still debatable, and the generic/subgeneric structure of Miltochrista sensu lato needs revision (Volynkin et al., in prep.).